INVESTIGATION ON PHARMACOGNOSY OF KATHA POWDER AS WELL AS IT’S IN VITRO CYTOTOXIC ACTIVITY - SHARMA, PANKAJ (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objective: The present study delves into the investigation of quantitative phytochemical in Katha powder, and it is in vitro cytotoxic activity. Methods: Coarsely dried chips of Acacia catechu heartwood were treated with a 10% hydro-alcoholic solution to obtain Katha as the final product. The powdered Katha was standardized through pharmacognostic parameters. Phytochemical investigations were carried out to screen polyphenols (tannins and flavonoids) of interest which later were confirmed by thin-layer chromatography. The cytotoxicity effect of Katha powder on MCF-7, A431, and HepG2 cells was characterized by the trypan blue dye exclusion and MTT colorimetric assays technique. Control assay was carried out for samples containing only the appropriate volumes of blank solutions and showed no effect on cell growth. Different cells were exposed to Katha powder for about 48 h and performed cytotoxicity assays. The effect of Katha powder against these cell lines concentration range 10–100 μg/ml showed a decrease in percent cell viability in a dose-dependent manner, as compared with that of the control when examined by the trypan blue exclusion assay technique and MTT colorimetric assays technique. Results: Quantitative phytochemical investigations were showed that Katha is rich in the content of polyphenols (tannins and flavonoids) and having good pharmacological potential. The effect of Katha powder against these cell lines concentration range 10–100 μg/ml showed a decrease in percent cell viability in a dose-dependent manner. Conclusion: So from this investigation it is to be suggested that the Katha powder is rich in the phenolic compound and shows a good anticancer effect against MCF-7, A431, and HepG2 cells.